Effect of Physical Activity and Hippocampal Learning Performance (Docentes 2.0 Journal, 2021)
The lifestyle of man has been characterized since inception by the different manifestations of physical activity in their daily work. A reference to contextualize the importance of it in the university environment is to contrast the variables of harmful behaviors such as inappropriate study habits and low capacity for understanding in academic settings as factors that affect academic performance by students. The objective of this work described the effect of physical activity as hippocampal behavior associated with a theoretical account in university students from faculties of material culture, sports, recreation, Bucaramanga section. This study was designed with a quasi-experimental emphasis as a one-month intervention protocol through interactive digital platforms Microsoft teams, in conjunction with specialized software (MATLAB). A numerical computing system gave rise to an Integrated development environment with its programming language, adaptable to other platforms such as Windows. On this occasion, 57 healthy participants developed, through a series of codes, different evaluable patterns, the measurement of hippocampal-dependent learning abilities in a visual search task "T," in correlation with the effect of activity variables. Physics is regulated with its high oxygen demand at the physiological or cerebral level.
Keywords: Physical activity; neuroscience; education